Microsoft Windows Communication Foundation 4.0 cookbook for developing SOA applications - Cheng, Steven (Packt Pub., 2010)
In Detail The Windows Communication Foundation 4.0 (WCF 4.0) is a .NET-based application programming interface for building and running connected systems. It enables secure and reliable communication among systems within an organization or across the Internet. This book deals with the difficult issues faced by a .NET developer while working with WCF. WCF 4.0 is a communications infrastructure that unifies a broad array of distributed systems' capabilities in a composable, extensible architecture that supports multiple transports, messaging patterns, encodings, network topologies, and hosting models. This book is a collection of focused real-world recipes and covers basic recipes on topics such as working with contracts to more advanced topics such as extending WCF runtime. By the end of this book you will have valuable information that helps transform the potentially unproductive habits of .Net developers who work with WCF. This book will take you through many concepts starting with complete support for contract-related design for WCF service development. You will learn to use WCF's built-in feature for building various service endpoints. Service hosting and configuration are important areas for building WCF services, especially at the service deployment stage, and are detailed in this book. You will find it easy to work with WCF client proxy generation and metadata publishing and discovery when you go through recipes such as customizing auto-generated service proxies. The author then discusses the exchange of data in WCF service operation features, related to WCF data serialization. You will discover some useful tips for security in WCF service development and built-in features for developing concurrency control for your services built upon it. One big plus is that you will learn to extend the existing WCF framework to achieve advanced functionality. You will find a dedicated chapter for RESTful and AJAX-enabled service development. Moving on, you will find several useful WCF service interoperability cases, which are important for a distributed service development platform. Towards the end of this book you will find some handy and useful diagnostic methods for troubleshooting. Extend and secure the WCF framework and develop robust SOA applications with easeApproach The recipes in this book are easy to understand and follow as the author discusses real-world scenarios. The range of topics covered in this book will bring out the forward-thinking WCF developer in you. It is not a comprehensive reference to the whole of WCF, but a practical guide that boosts proficiency when working with the various features of WCF. The examples are supported by relevant background information for ease of understanding. Who this book is for If you work with Windows Communication Foundation 4.0 and you want to be efficient when working with WCF features such as interoperability, proxy generation, and security, you will find this book very useful. With this book you will be able to find quick and handy solutions for various kinds of service development scenarios using Microsoft Windows Communication Foundation 4.0. To follow the recipes you will need to be comfortable with .NET Framework, C♯ programming, and the basics of SOA and how to develop them.